2006
DOI: 10.4028/www.scientific.net/msf.503-504.967
|View full text |Cite
|
Sign up to set email alerts
|

Hardening Mechanisms of Metals and Alloys Produced by SPD

Abstract: Strengthening is a complex process involving such basic mechanisms as dislocation accumulation (work hardening), Hall-Petch hardening due to grain refinement, solid solution hardening and precipitation hardening in various combinations. The contribution of different mechanisms into resultant strength can vary significantly depending on chemical composition and processing. The purpose of the present work is to explore the significance of SPD for hardening and to clarify the role of different strengthening mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, the observation in Figure 12 suggested that the hardness distribution of 120º sample was less homogenous compared to 126º, even though its average hardness is higher. Therefore, increasing the die angle can lead to a decrease in strain magnitude but the strain induced is more homogeneous throughout the samples [31].…”
Section: Effect Of Die Angle and Number Of Press To Peeqmentioning
confidence: 99%
“…However, the observation in Figure 12 suggested that the hardness distribution of 120º sample was less homogenous compared to 126º, even though its average hardness is higher. Therefore, increasing the die angle can lead to a decrease in strain magnitude but the strain induced is more homogeneous throughout the samples [31].…”
Section: Effect Of Die Angle and Number Of Press To Peeqmentioning
confidence: 99%